Tata Laksana Onikomikosis Candida: Tinjauan Pustaka - Imma Irfani, Qonita (PT Kalbe Farma Tbk., 2025)
Onychomycosis, also known as tinea unguium, is a fungal infection of the nail that can be caused by various types of fungi, including dermatophytes, non-dermatophyte molds, and yeasts. One specific type is candidal onychomycosis, which is caused by yeasts, particularly those from the Candida genus. This nail infection may affect all parts of the nail unit, including the nail plate, matrix, and surrounding tissue. Common clinical manifestations include nail discoloration—typically yellow or brown—thickening or softening of the nail, and increased nail fragility. Onychomycosis is one of the most frequently encountered nail disorders, with an estimated prevalence of approximately 50% of all complaints related to nail disease. Given the diverse etiologies of nail infections and broad differential diagnoses, laboratory examination is strongly recommended prior to initiating treatment. Diagnostic methods such as direct microscopy, fungal culture, and molecular testing are essential for accurate identification, enabling more targeted, effective, and cost-efficient therapy.